Remote sensing in inventory of high altitude pastures of the eastern Tibetan Plateau - Kumpula, Timo; Colpaert, Alfred; Qian, Wang; Manderscheid, Angela (Rangifer, 2004)
The animal husbandry practised on high altitude pastures of the eastern Tibetan Plateau is based on the use of natural pastures. The livestock consists of yaks, sheep and horses. During the recent decades the number of animals has increased in the Dzoge study area, which is located in the north western part of the Sichuan province at an altitude of 2800-4000 meters. Most of Dzoge is treeless grassland with large peat land areas. The remote sensing and Geographical Information System (GIS) methods combined with the conventional pasture mapping provide a methodology to make a cost effective and reliable inventory of large areas. Providing accurate data about the quality and quantity of pastures and also of the amount of natural forage resources promotes sustainable use of the pastures. Two field trips were made to Dzoge. Random test plots (186) covering the main vegetation types in the research area were selected. The Landsat TM image is the remote sensing data in used this study. The image classification was done in the ERMapper program. The final map producing and the accuracy assessment were performed in the ArcGIS program. The Landsat TM image proved to be a useful data source in the mapping of pastures in the Dzoge area. The main vegetation classes were classified accurately. The estimations of the biomass of different vegetation types were made. Elevation differences were relatively small and the shadows on the slopes did not affect the classification significantly.